2009 IEEE/RSJ International Conference on Intelligent Robots and Systems 2009
DOI: 10.1109/iros.2009.5354271
|View full text |Cite
|
Sign up to set email alerts
|

Stable whole-body motion generation for humanoid robots to imitate human motions

Abstract: Abstract-This work presents a methodology to generate dynamically stable whole-body motions for a humanoid robot, which are converted from human motion capture data. The methodology consists of the kinematic and dynamical mappings for human-likeness and stability, respectively. The kinematic mapping includes the scaling of human foot and Zero Moment Point (ZMP) trajectories considering the geometric differences between a humanoid robot and a human. It also provides the conversion of human upper body motions us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Kim et al [8] investigated how to keep the stability when converting a motion from a human to a robot. This study used a complex calculation that confirmed the stability of the robot, both kinetically and dynamically.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Kim et al [8] investigated how to keep the stability when converting a motion from a human to a robot. This study used a complex calculation that confirmed the stability of the robot, both kinetically and dynamically.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The errors caused by model error and environment disturbance are eliminated utilizing posture balance algorithm [1]. Due to high-performance trajectory tracking of electrical motors, many humanoid robots are capable of stable walking and running [2,3]. However, these robots tend to be energetically inefficient and brittle against terrain disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The general pipeline of balance maintenance involves designing ZMP trajectory for a humanoid robot, computing reference CoM trajectory from the ZMP trajectory, and constraining a humanoid robot to follow the reference CoM trajectory. Kim et al [23] proposed a method for imitating full body dance movements. The ZMP trajectory of the robot was generated based on the support region and used to compute reference CoM trajectory by recursive equations.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, several methods which performed optimization to minimize error between movements of human and a humanoid robot and interpolation between discrete time points have been proposed [16,19,20,21]. For example, Kim et al [23] optimized joint angle trajectories to minimize error between movements of human and a humanoid robot; then applied spline interpolation to smooth angle trajectories of upper body. Boutin et al [26] formulated inverse kinematics as an optimization problem to find joint angles for walking that satisfy motion constraints.…”
Section: Introductionmentioning
confidence: 99%